Analysis of diesel spray characteristic using single hole SAC nozzle and VCO nozzle - Mohd Fazwan, Ishak (2012)
This study was focus to investigate the diesel spray characteristics and atomization performance. The influences of injector nozzle geometry and injection pressure conditions on a diesel fuel spray were examined and predicted by using ANSYS FLUENT software. A flow domain and constant volume combustion chamber was designed and temperature was set 540 K at pressure 1 MPa for simulations. Spray penetration length and cone angle of diesel spray were recorded. To investigate the influence of nozzle geometry, Sac and VCO (Valve Covers Orifice) with difference diameter orifice and injection pressure were designed and used in both spray evolution. Comparisons were made between different nozzle geometries and different injection pressures. Differences were observed between VCO and Sac nozzles, with the Sac nozzles showing a higher rate of penetration under the same conditions.